A Reflection on Spiritual Development of Students as Part of Holistic Education in Ghana: A Christian’s Perspective - Godfred Adjei Nyarko (E-Journal of Religious and Theological Studies, 2020)
The development of students’ spirituality as part of their formation was found to be important by the early missionaries who started formal education in the country. This was because they had the belief that good education is one of the pivots necessary for the progress and development of any society and nation. Education encompasses all round development of a person which embodies both the physical and spiritual aspects of life. However, of late the continuous educational reforms which have been implemented in Ghana have neglected the spiritual development of students, relegating it to the background in terms of making it an integral part of the formal educational curriculum. Any education devoid of the right moral values is self-destructive and detrimental to development. The youth who form majority of the nation’s population are confronted with numerous challenges and the need for their spiritual development as part of holistic education is very critical. This has brought about the continuous debate as to whether spiritual development or spirituality should be integrated into Ghana’s educational system as part of students’ formation. The purpose of this paper is to find out the effect of spiritual development on students’ holistic education and how spirituality impact teaching and learning. It will also consider some Christian religious practices as part of spiritual development, and how these religious expressions influence students’ holistic formation.